2020
DOI: 10.1002/onco.13574
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Neoadjuvant Carboplatin and Nab-Paclitaxel in Patients with Triple-Negative Breast Cancer

Abstract: Background. In this phase II clinical trial, we evaluated the efficacy of the non-anthracycline combination of carboplatin and nab-paclitaxel in early stage triple negative breast cancer (TNBC). Patients and Methods. Patients with newly diagnosed stage II-III TNBC (N=69) were treated with neoadjuvant carboplatin (AUC 6) every 28 days x 4 plus nab-paclitaxel (100 mg/m 2) weekly for 16 weeks. Pathological complete response (pCR) and residual cancer burden (RCB) were analyzed with germline mutation status, tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 66 publications
1
25
0
Order By: Relevance
“…Three pathologists (ES, AR, and EB) evaluated 204 cases, and the remaining cases were evaluated by a single pathologist (ES) with a consensus reached with the other two pathologists in difficult cases. We used the manual sTIL status as a continuous variable when possible and with a cutpoint of >10% [ 21 , 39 , 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Three pathologists (ES, AR, and EB) evaluated 204 cases, and the remaining cases were evaluated by a single pathologist (ES) with a consensus reached with the other two pathologists in difficult cases. We used the manual sTIL status as a continuous variable when possible and with a cutpoint of >10% [ 21 , 39 , 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…In BrighTNess, the addition of carboplatin increased the pCR rate in BRCAwildtype patients from 29 to 59%, versus an increase from 41 to 50% in BRCA carriers. 51 Additionally, in GeparSixto, there was an absolute improvement in DFS at 35 months with the addition of carboplatin, which was greater in BRCA-wildtype patients (85 versus 74%; HR 0.53; 95% CI 0.29-0.96), versus in BRCA-mutated patients (86 versus 82%). 53,54 Although the addition of platinum to a NACT regimen leads to higher pCR rates, the associated toxicities often necessitating dose reductions or cycle eliminations and the contradictory longterm survival results make it a controversial choice.…”
mentioning
confidence: 94%
“…In contrast, the GeparSixto trial demonstrated that the addition of carboplatin significantly improved pCR (53% vs 43%, p=0.005) which resulted in higher rates of 3-year EFS (86% vs 76%, HR of 0.60, 95% CI 0.34-0.93). 51 In the BrighTNess study, patients with stage II to III TNBC were randomized to weekly paclitaxel with or without carboplatin and veliparib (an oral PARP inhibitor) followed by doxorubicin and cyclophosphamide. The addition of carboplatin improved the pCR rate from 31% to 58% while the addition of veliparib had no effect on pCR rates.…”
mentioning
confidence: 99%
“…Figure1. An overview of the main biomarkers for immunotherapy in breast cancer 18. F-FDG,18 F-fluorodeoxyglucose; HRD, homologous recombination deficiency; LDH, lactate dehydrogenase; MMR, mismatch repair; NLR, neutrophil-to-lymphocyte ratio; PD-1, programmed cell death-1; PD-L1, programmed death-ligand 1; PET, positron emission tomography; PLR, platelet-to-lymphocyte ratio; TILs, tumour infiltrating lymphocytes; TLSs, tertiary lymphoid structures; TMB, tumour mutational burden.…”
mentioning
confidence: 99%
“…CyTOF, cytometry by time of flight; F-FDG,18 F-fluorodeoxyglucose; H&E, haematoxylin and eosin; HRD, homologous recombination deficiency; ICIs, immune checkpoint inhibitors; IF, immunofluorescence; IHC, immunohistochemistry; LDH, lactate dehydrogenase; MSI/dMMR, microsatellite instability/mismatch repair deficiency; NLR, neutrophil-tolymphocyte ratio; OS, overall survival; PD-1, programmed cell death-1; PD-L1, programmed death-ligand 1; PET, positron emission tomography; PFS, progression free survival; PLR, platelet-to-lymphocyte ratio; POLE, polymerase epsilon; TILs, tumour-infiltrating lymphocytes; TLS, tertiary lymphoid structure; TMB, tumour mutational burden; TME, tumour microenvironment.…”
mentioning
confidence: 99%